2002
DOI: 10.1046/j.1472-765x.2002.01079.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of LST + MUG broth technique and conventional method for the enumeration of Escherichia coli in foods

Abstract: Aims: To reduce the analysis time needed for the enumeration of Escherichia coli, a rapid fluorogenic method (MUG) which takes only 48 h was compared with the standard most probable number (MPN) method which takes 6 days as described in the International Standards Organization (ISO). This study provides reliability data for the fluorogenic method applied to certain foods. Methods and Results: Both methods were applied to 500 food samples which were analysed for E. coli enumeration. Agreement between the two me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Measurement of the E. coli populations is the best indicator of the fecal contamination of both water (Edberg et al, 2000) and foods (Dogan et al, 2002). Since total commensal E. coli is also an accurate indicator of E. coli O157:H7 environmental persistence (Ogden et al, 2001), we measured the total E. coli population.…”
Section: Methodsmentioning
confidence: 99%
“…Measurement of the E. coli populations is the best indicator of the fecal contamination of both water (Edberg et al, 2000) and foods (Dogan et al, 2002). Since total commensal E. coli is also an accurate indicator of E. coli O157:H7 environmental persistence (Ogden et al, 2001), we measured the total E. coli population.…”
Section: Methodsmentioning
confidence: 99%
“…Here, 500 food samples which were analysed for E. coli enumeration. This study came with results that fluorogenic method is more reliable and shorter to perform than the standard ISO method [20].…”
Section: Analysis Of Raw Milk and Pasteurized Milk Samples By Develop...mentioning
confidence: 84%
“…In some studies on this subject, Rice et al (1990) reported that E. coli strains isolated from a total of 460 human, 105 cows and 55 horses were screened and 95.5% β-glucuronidase-positive were isolates in 24 h and 99.5% positive after 28 h of incubation. Doğan and Halkman (1998) isolated 190 E. coli strains in the studies and they reported that all colonies gave the fluorescent positive in LST + MUG media. In our study, it was also confirmed that a total of 40 isolates were consisted of E. coli species according to biochemical characteristics and β-glucuronidase activities.…”
Section: Discussionmentioning
confidence: 99%